2018
DOI: 10.1017/neu.2018.34
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Y and religious commitment in healthy young women

Abstract: ObjectiveThe present study explores the relationship between neuroactive hormones and religious commitment. We hypothesised that religious commitment is mediated by neuropeptide Y and oxytocin. These neurohormones have a well-established role in general well-being, anxiety regulation, stress-resilience, social affiliation and spirituality.MethodsSixty healthy women (median age 21) participated in the study and completed the Religious Commitment Inventory and other psychometric surveys. Blood was sampled from e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 64 publications
(80 reference statements)
0
2
0
Order By: Relevance
“…We analysed the relationship between OC use and hormones using two previously published datasets 46,47 . Both studies were similar methodologically and the current study includes only women who identified their birth control method.…”
Section: Methodsmentioning
confidence: 99%
“…We analysed the relationship between OC use and hormones using two previously published datasets 46,47 . Both studies were similar methodologically and the current study includes only women who identified their birth control method.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, neuropeptides are important regulators of social behavior and bonding ( Meyer-Lindenberg et al, 2011 ), making them of direct relevance to the social dimension of resilience, particularly in the context of the COVID-19 pandemic where social distancing, quarantine, and reduced social support all exert a negative impact on the mental health of healthcare workers ( da Silva and Neto, 2020 ). Specific neuropeptides have also been strongly correlated with individual variations, religious, and spiritual beliefs ( Imamura et al, 2017 ; Tonnesen et al, 2018 ), suggesting that – uniquely among the mechanisms discussed thus far – they are also related to the meaning dimension of resilience. In other words, from a conceptual viewpoint, neuropeptides are implicated in all three of Feldman’s postulated dimensions of resilience.…”
Section: Key Research Areas In the Neurobiology Of Resilience And Thementioning
confidence: 98%